2017
DOI: 10.1021/acs.analchem.7b01443
|View full text |Cite
|
Sign up to set email alerts
|

Unique Approach To Develop Carbon Dot-Based Nanohybrid Near-Infrared Ratiometric Fluorescent Sensor for the Detection of Mercury Ions

Abstract: The ratiometric fluorescence assay, which can eliminate the external effects, has attracted great attention. In this work, a carbon dot (CD)-based nanohybrid dual-emission system was simply prepared by a unique approach of solvothermal treating corn bract and used as a ratiometric fluorescent sensor for Hg detection. Under a single excitation, the obtained nanohybrid sensor had two emission bands around 470 and 678 nm, which may originate from the intrinsic structure of CDs and chlorophyll-derived porphyrins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 207 publications
(97 citation statements)
references
References 35 publications
1
95
0
Order By: Relevance
“…This observation was supported by previous literature ,. Moreover it has been reported that Hg 2+ can quench the fluorescence of carbon dot through the interaction with electron‐rich aromatic ring . Thus, the slight decrease in fluorescent intensity of GQD from AuQC@GQD in the presence of Hg 2+ can be due to the electron transfer from electron‐rich aromatic ring of GQD and Hg (II).…”
Section: Resultssupporting
confidence: 88%
“…This observation was supported by previous literature ,. Moreover it has been reported that Hg 2+ can quench the fluorescence of carbon dot through the interaction with electron‐rich aromatic ring . Thus, the slight decrease in fluorescent intensity of GQD from AuQC@GQD in the presence of Hg 2+ can be due to the electron transfer from electron‐rich aromatic ring of GQD and Hg (II).…”
Section: Resultssupporting
confidence: 88%
“…Figure a and b give the TEM image and size distribution of the prepared CQDs sample. From TEM image, it can be seen that the CQDs sample has uniform particle size with diameter of 2.5 nm, and the lattice spacing is about 0.25 nm (HRTEM insert), similar to the graphite (100) crystal facet . The corresponding size distribution curve exhibits a single peak, indicating that the CQDs sample is well dispersed.…”
Section: Resultsmentioning
confidence: 99%
“…At excitation wavelength of 420 nm, the CQDs solution exhibits the strong fluorescence emission (curve 3) and two emission peaks located at 506 and 676 nm are visible. The former may be from the intrinsic structure of CQDs and the latter is similar to the characteristic emission peak of the porphyrin derivative …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations